Factors influencing infection and transmission of Anopheles gambiae densovirus (AgDNV) in mosquitoes - Tapan K. Barik; Yasutsugu Suzuki; Jason L. Rasgon (PeerJ, 2016)
Anopheles gambiae densovirus (AgDNV) is a potential microbial agent for paratransgenesis and gene transduction in An. gambiae, the major vector of human malaria in sub-Saharan Africa. Understanding the interaction between AgDNV and An. gambiae is critical for using AgDNV in a basic and applied manner for Anopheles gene manipulation. Here, we tested the effects of mosquito age, sex, blood feeding status, and potential for horizontal transmission using an enhanced green fluorescent protein (EGFP) reporter AgDNV system. Neither mosquito age at infection nor feeding regime affected viral titers. Female mosquitoes were more permissive to viral infection than males. Despite low viral titers, infected males were able to venereally transmit virus to females during mating, where the virus was localized with the transferred sperm in the spermathecae. These findings will be useful for designing AgDNV-based strategies to manipulate Anopheles gambiae.